(untitled) (Educational Perspectives Magazine (REPED), 2023)
This article tries to establish a practical/theoretical reflection about the “pedagogical knowledge” which should be inserted in programs of teacher training, with the aim of contributing to the training of an educational professional who develops educational quality with their future students. In order to initiate this reflection, we start from two previous considerations which, to our understanding, sitúate the processes of teacher training in Chile. These are related to the political/ educational scenarios which are installed in our society with the social movement of secondary school students, since May 2006, and to the political and institutional backgrounds which have to be taken into account in our country when we want to effectively improve the quality of public education.